Inhibition of autophagy limits vertical transmission of Zika virus in pregnant mice - Cao, Bin; Parnell, Lindsay A.; Diamond, Michael S.; Mysorekar, Indira U. (The Journal of experimental medicine, 2017)
Zika virus (ZIKV) infection during pregnancy leads to devastating fetal outcomes, including intrauterine growth restriction and microcephaly. Greater understanding of mechanisms underlying ZIKV maternal-fetal transmission is needed to develop new therapeutic interventions. Here, we define an important role for the autophagy pathway in ZIKV vertical transmission. ZIKV infection induced autophagic activity in human trophoblasts and pharmacological inhibition limited ZIKV infectivity. Furthermore, deficiency in an essential autophagy gene, Atg16l1, in mice limited ZIKV vertical transmission and placental and fetal damage and overall improved placental and fetal outcomes. This protection was due to a placental trophoblast cell-autonomous effect of autophagic activity, not to alterations in systemic maternal ZIKV infection. Finally, an autophagy inhibitor, hydroxychloroquine, approved for use in pregnant women, attenuated placental and fetal ZIKV infection and ameliorated adverse placental and fetal outcomes. Our study reveals new insights into the mechanism of ZIKV vertical transmission and suggests that an autophagy-based therapeutic warrants possible evaluation in humans to diminish the risks of ZIKV maternal-fetal transmission.